2016
DOI: 10.1177/1745691615621272
|View full text |Cite
|
Sign up to set email alerts
|

Social Identities in a Globalized World

Abstract: Globalization-the increasing interconnectedness of societies, economies, and cultures-is a defining feature of contemporary social life. Paradoxically, it underlies both the dynamics of global crises (e.g., rising inequality, climate change) and the possibilities for ameliorating them. In this review, we introduce globalization as a multifaceted process and elaborate its psychological effects with respect to identity, culture, and collective action. Using a social identity approach, we discuss three foci of id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 111 publications
(186 reference statements)
2
27
0
2
Order By: Relevance
“…For pro‐social behavior, McFarland and colleagues () found correlations of identification with all humanity with the readiness to invest national resources to protect human rights and even with the readiness to donate to a charity. Comparable findings also suggest a consistent relationship between the identification with humanity and pro‐social (e.g., Reese & Kohlmann, ) as well as sustainable actions (e.g., Renger & Reese, ; Reysen & Katzarska‐Miller, ; Rosenmann, Reese & Cameron, ).…”
Section: The Superordinate Identity Of Humanitymentioning
confidence: 82%
See 3 more Smart Citations
“…For pro‐social behavior, McFarland and colleagues () found correlations of identification with all humanity with the readiness to invest national resources to protect human rights and even with the readiness to donate to a charity. Comparable findings also suggest a consistent relationship between the identification with humanity and pro‐social (e.g., Reese & Kohlmann, ) as well as sustainable actions (e.g., Renger & Reese, ; Reysen & Katzarska‐Miller, ; Rosenmann, Reese & Cameron, ).…”
Section: The Superordinate Identity Of Humanitymentioning
confidence: 82%
“…In Study 2, we replicated this effect with real contacts, in a longitudinal data set with two time points. Both studies thereby contribute substantially to the work on global identity and identification with all humanity (McFarland, ; McFarland, Brown & Webb, ; McFarland, Webb & Brown, ; for an overview, see Rosenmann et al, ). In addition, Study 2 showed that international contact (Time 1) mediated through higher global identification (Time 2) was positively related to intentions to act in line with global responsibility (general attitudes on global responsibility, pro‐refugee attitudes; both at Time 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hints at the possibility of considering such intergroup processes in understanding the influence of culture or cultural identity, an area to be explored particularly with increasing globalization fostering multiculturalism and influencing intergroup relations (and possibly conflicts; Kinnvall, 2004;Rosenmann, Reese, & Cameron, 2016;Verkuyten & Pouliasi, 2006).…”
Section: Mattersmentioning
confidence: 99%